2009
DOI: 10.1176/ps.2009.60.8.1046
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence: A Literature Review and Conceptual Model for Mental Health Services

Abstract: This article presents a conceptual model of organizational cultural competence for use in mental health services that resulted from a comprehensive review of the research literature. The model identifies four factors associated with cultural competence in mental health services (community context, cultural characteristics of local populations, organizational infrastructure, and direct service support) and redefines cultural competence as the degree of compatibility among these factors. A strength of this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 32 publications
5
56
0
Order By: Relevance
“…Culturally competent agencies incorporate culturally sensitive evidence-based treatments and culturally specific interventions whenever possible. Culturally competent systems of care (the final level) reflect meaningfully the issues within the communities they purport to serve (Hernandez, Nesman, Mowery, Accevedo-Polakovich, & Callejas, 2009). This includes effective and essential language-appropriate outreach and coordination with emergency service agencies (i.e., police and fire, schools, homeless shelters, women's centers, and hospitals).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Culturally competent agencies incorporate culturally sensitive evidence-based treatments and culturally specific interventions whenever possible. Culturally competent systems of care (the final level) reflect meaningfully the issues within the communities they purport to serve (Hernandez, Nesman, Mowery, Accevedo-Polakovich, & Callejas, 2009). This includes effective and essential language-appropriate outreach and coordination with emergency service agencies (i.e., police and fire, schools, homeless shelters, women's centers, and hospitals).…”
mentioning
confidence: 99%
“…Sue, Arrendondo & McDavis, 1992). Recent conceptualizations, however, view cultural competence within the context of the community behavioral health delivery system itself (Gamst et al, 2011;Hernandez et al, 2009). Therefore, cultural competence is seen as the "the degree of compatibility between the cultural and linguistic characteristics of a community and the manner in which the combined policies, structures, and processes underlying local mental health services seek to make these services available, accessible, and utilized" (Hernandez et al, 2009(Hernandez et al, , p. 1047.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of education, burnout, and MCC and clinicians’ race appear less important than general experiences and relationships with people from other racial and ethnic groups. Perhaps factors embedded in community dynamics or organizational functioning also play a role, along with experiences and relationships, in shaping clinicians’ ability to work effectively with black and white patients (10,45). …”
Section: Discussionmentioning
confidence: 99%
“…Two clinician factors are frequently posited to either produce or ameliorate outcome differences for black patients: clinicians’ level of multicultural counseling competency (MCC) and their race (3,8-10). In a content analysis covering 20 years of MCC research, Worthington and colleagues (11) found some evidence that such competence improves clinicians’ skills with patients from nonwhite racial-ethnic and cultural minority groups.…”
mentioning
confidence: 99%